2022
DOI: 10.3389/fenvs.2022.913835
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Carbon Dioxide Emissions and Their Peaking Prospect: Evidence From China

Abstract: In order to examine the key determinants of carbon dioxide emissions and judge whether China’s carbon dioxide emissions can reach their peak value before 2030, this study first uses the extended STIRPAT model to analyze the determinants of China’s carbon dioxide emissions from 1995 to 2019 and then uses the model regression result to forecast the carbon dioxide emissions from 2020 to 2040 under six scenarios to investigate their prospect. It is found that population size, GDP per capita, energy intensity, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Existing studies have shown that population, energy structure, and industrial structure all have positive impacts on carbon emissions. 58,29 The results show that the population (0.034), industrial structure (0.1267), and energy structure (0.0457) positively correlate with carbon emissions. These results are consistent with existing research results.…”
Section: Discussionmentioning
confidence: 95%
“…Existing studies have shown that population, energy structure, and industrial structure all have positive impacts on carbon emissions. 58,29 The results show that the population (0.034), industrial structure (0.1267), and energy structure (0.0457) positively correlate with carbon emissions. These results are consistent with existing research results.…”
Section: Discussionmentioning
confidence: 95%
“…Analyzing the migration trajectory for the center of gravity is therefore a useful means of analyzing the spatial and temporal patterns of the element. Many studies have also used this method to assess the transfer of carbon emissions Zhao et al, 2022):…”
Section: Gravity Center Shiftmentioning
confidence: 99%
“…There is a large difference between the cost of carbon emissions reduction in developed and developing countries, which can lead to a large difference in the effectiveness of the implemented actions to reduce carbon emissions (Li et al, 2015). Population size is one of the most important factors to affect carbon dioxide emissions, and differences in population size mean that the same targets have different implications when applied to countries with different population sizes (Zhao et al, 2022). It is unreasonable to measure the reduction in carbon emissions from a country only from the total emissions.…”
Section: Introductionmentioning
confidence: 99%
“…As the main contributor to global warming and environmental pollution, enterprises play a critical role in carbon emissions reduction (Chen et al, 2022;Jiao et al, 2022;Zhang et al, 2022;Zhao et al, 2022). Therefore, enterprises should take on more responsibilities for reducing carbon emissions (Besio and Pronzini, 2014;Haney, 2017).…”
Section: Introductionmentioning
confidence: 99%